Sustainable Procurement in Australia: Quantity Surveyors' Perception on Life Cycle Costing - Lim, Benson Teck Heng; Zhang, Waning; Oo, Bee Lan (International Journal of Integrated Engineering, 2018)
Life cycle costing (LCC) has long been recognised as one of the essential techniques for sustainable development. Over the past decades, the use of LCC in the industry has been restricted and building stakeholders are blaming each other for its limited application. The research aims to investigate quantity surveyors'perception towards LCC implementation in Australia by specifically examining their general awareness and application of LCC; determining the key obstacles hindering LCC implementation; and identifying the key enablers for LCC implementation. An online survey of 24 quantity surveying professionals was undertaken. The overall results indicate that quantity surveying professionals do have basic knowledge of LCC and appreciate its benefits. However, the results suggest that clients and architects are the key culprits for hindering the implementation of LCC by placing greater emphasis on initial costs and design over strategic value of an asset. For wider application, it is suggested that government and professional bodies play a vital role to enforcing and promoting the future use of LCC. In conclusion, the research informs building stakeholders the key issues in LCC implementation and adds to the existing body of knowledge on LCC application for future research to be undertaken.